In the Eye of the Storm: Israeli Psychoanalysis and its Political Surroundings. (8th June 2015) - Berman, Emanuel
Abstract This paper discusses the historical and political context in which Israeli analysts and therapists practice, particularly emphasizing the Israeli‐Arab conflict and its traumatic influence. It proposes a potential role psychoanalytic understanding can play in detoxifying the most destructive aspects of the conflict, especially if non‐judgmental empathy to the emotional experience of both sides can lead beyond moralistic splitting into "good" and "evil" and beyond a "doer and done‐to" dichotomy. Copyright © 2015 John Wiley & Sons, Ltd.